2016
DOI: 10.1016/j.ijsu.2016.06.034
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the Cook-Swartz Doppler with conventional clinical methods for free flap monitoring: A systematic review and a meta-analysis

Abstract: More studies are needed to evaluate if Cook-Swartz Doppler can be used alone, or to be better used as an adjunctive technique to complement the clinical method of monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…In general, vascular complications predominantly occur in the first 48 hours postsurgery and the flap salvage outcome within this period is superior to after this period . In the control group, only 1 case exhibited abnormal findings within the first 48 hours.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In general, vascular complications predominantly occur in the first 48 hours postsurgery and the flap salvage outcome within this period is superior to after this period . In the control group, only 1 case exhibited abnormal findings within the first 48 hours.…”
Section: Discussionmentioning
confidence: 96%
“…In case of an implantable Doppler, there are conflicting reports about its benefits in improving flap survival . A meta‐analysis determined that it can improve flap survival . However, it indicated that there was a greater frequency of false positives than with conventional monitoring .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, implantable Doppler devices may dislodge, malfunction, or injure an anastomosis upon removal . Furthermore, an increase in false‐positive rates of vascular occlusion detection have been reported . Lastly, other emerging noninvasive modalities for measuring oxygen such as photoacoustic imaging and paint‐on bandages, though useful in the right situation, harbor inherent weaknesses.…”
Section: Discussionmentioning
confidence: 99%